Pengaruh Penerapan Pembelajaran Blended Learning terhadap Hasil Belajar Siswa - Zulma Hendra; Alfi Yunita; Ainil Mardiyah (Horizon, 2021)
ABSTRACT This study aims to determine the effect of the application of blended learning on the learning outcomes of class X MIA students at SMA PGRI 2 Padang. This study used a pre-experimental design in the form of a One-Shot Case Study by taking research subjects by Purposive Sampling. The sample of this research was the students of class X MIA. This study used descriptive questions as a final test instrument. The data analysis technique used in this research was a t-test. Based on the data collection techniques and data analysis carried out, it was obtained that tcount = 1.81 and ttable = 1.68, because tcount > ttable, then reject H0 at a significant level of 0.05 so it can be concluded that there is an effect of applying blended learning on studensts’ learning outcomes of class X MIA at SMA PGRI 2 Padang. Keywords: Blended Learning, Learning Outcomes